Global warming : - Archer, David, 1960- (John Wiley & Sons, 2012)
"Archer's Global Warming: Understanding the Forecast 2nd Edition, is the first real text to present the science and policy surrounding climate change at the right level. Accompanying videos, simulations and instructional support makes it easier to build a syllabus to improve and create new material on climate change. Archer's polished writing style makes the text entertaining while the improved pedagogy helps better understand key concepts, ideas and terms.This edition has been revised and reformulated with a new chapter template of short chapter introductions, study questions at the end, and critical thinking puzzlers throughout. Also a new asset for the BCS was created that will give ideas for assignments and topics for essays and other projects. Furthermore, a number of interactive models have been built to help understand the science and systems behind the processes" -- Από τον εκδότη.